The Emerging Role of Non-Coding RNAs in Drug Addiction - Sartor, Gregory C.; St. Laurent, Georges; Wahlestedt, Claes (Frontiers in Genetics, 2012)
Prolonged drug use causes long-lasting neuroadaptations in reward-related brain areas that contribute to addiction. Despite significant amount of research dedicated to understanding the underlying mechanisms of addiction, the molecular underpinnings remain unclear. At the same time, much of the pervasive transcription that encompasses the human genome occurs in the nervous system and contributes to its heterogeneity and complexity. Recent evidence suggests that non-coding RNAs (ncRNAs) play an important and dynamic role in transcriptional regulation, epigenetic signaling, stress response, and plasticity in the nervous system. Dysregulation of ncRNAs are thought to contribute to many, and perhaps all, neurological disorders, including addiction. Here, we review recent insights in the functional relevance of ncRNAs, including both microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), and then illustrate specific examples of ncRNA regulation in the context of drug addiction. We conclude that ncRNAs are importantly involved in the persistent neuroadaptations associated with addiction-related behaviors, and that therapies that target specific ncRNAs may represent new avenues for the treatment of drug addiction.